The United Kingdom's School Asset Management Plans - Jones, Alan (PEB Exchange, Programme on Educational Building, 1999)
Provisional Guidance on Asset Management Plans (AMPs) for schools was published by the Department for Education and Employment (DfEE) in August 1998. These plans will help English Local Education Authorities (LEAs) to identify, agree and address the most urgent and important priorities in their school capital programmes, and to help in their longer term planning and management of the school estate. They will also help to underpin LEA applications to DfEE for capital support